ANALYSIS OF DECISION SUPPORT SYSTEM HELPS IN MANAGERIAL DUTIES IN MARKETING INDONESIA PT BORSUMIJ WEHRY PROGRAM THROUGH MICROSOFT EXCEL - Mayu Sofia Mandiri; Aqwam Rosadi K. SKom. MM (Jurnal Sistem Informasi, 1999)
Company Borsumij Wehry Indonesia is a multi division and a geigrafis spread, andvertically integrated as the distribution of canned food. This company is typical oftoday's companies, namely, that the mobilization of resources from differentorganizations is directed to the various markets for the benefit of shareholders groups.But such cases are not common characteristics of many who owned the majority ofcompanies, ie able to profitably use the information system that processestransactions from 20 different organizations with a shared system and then submittedto the management company quickly. Will obtain the appropriate level ofprofitability, as well as control information to determine the basis for theorganization, perigkasan and compared with the plan.Top management received a brief report that shows the benefits of each organization,based on division and overall by a period and the current year, which compared withthe pla n.Section is responsible for marketing the contribution data submitted directly cost lessstandard. As far as the involvement of the marketing department, direct costs of thestandard is fixed. Therefore, this part of the answer can not be held accountable inmaximizing the contribution by varying the items that were under the control ofvolume, price, customer and product ingredients.The need for hardware and software continue to increase along with the rapiddevelopment of the computer at this time. A sophisticated hardware tida.